Creating your strategic plan : a workbook for public and nonprofit organizations - Bryson, John M. (John Moore), 1947- (Bryson on Strategic Planning., 2011)
"Creating Your Strategic Plan is the best-selling companion workbook to Bryson's landmark book, Strategic Planning for Public and Nonprofit Organizations. Whether used with the main text or by itself, this thoroughly revised third edition provides a step-by-step guide to putting strategic planning to work in public and nonprofit organizations. The workbook contains new and revised worksheets and additional material on readiness assessment, teamwork, stakeholder analysis, visioning, strategic issue identification, and implementation"--Provided by publisher